The Effectiveness of Cognitive Behavior Therapy Group Counseling with a Self-talk Technique to Improve the Body Image Satisfaction of Students with Social Media Addiction Tendencies - Shany Rusfa, Ullma; Mulawarman, Mulawarman; Sugiyo, Sugiyo (Jurnal Bimbingan Konseling, 2022)
Many social media users experience low Body Image Satisfaction (BIS) that results in anxiety, decrease in self-confidence, decrease in self-esteem, depression, and the drive to be thin. This study attempted to examine the effectiveness of CBT counseling with a self-talk technique to improve the BIS of students with social media addiction tendencies. It used a one group pretest-posttest design and involved 6 students whose data were collected using the instruments of body image satisfaction and social media addiction. Findings showed that the CBT group counseling with a self-talk technique has been effective to improve the BIS of students with social media addiction tendencies. Thus, counselors are recommended to implement the intervention of CBT group counseling with a self-talk technique to improve BIS, especially in senior high school students. Further studies are suggested to use a qualitative design to discover the impact of low BIS.